ELECTRONIC EDUCATION ON PRIMARY SCHOOLS - Peter, VIKTOR (Trends in education, 2010)
In this article we deal with electronic education, which we define as education with modern information and communication technologies. We orient on various ways of using IT on primary schools, especially on available educational software. Our attention is concentrate to advantages of their use and methodology of effective work with them. In practical part of article are information about our research and results. Main aim of research was verify efficiency of the educational process using digital content of software product LangMaster the School of Game.
Keywords: electronic education; information and communication technologies (ICT); interactive educational software; methodology of work with digital curriculum; efficiency of the educational process; pedagogical experiment.